An optimize canny algorithm with traditional machine learning for edge detection enhancement - Russel Lafta; Zainab Sultani (Engineering and Technology Journal)
Edge detection still represents a major challenge in image processing and computer vision because of the complexity and variability of real-world images. The canny algorithm is powerful in detecting edges. However, it is sensitive to noise, and as a result, may produce weak edges. The use of machine learning algorithms has significantly improved the performance of edge detection techniques. In this paper, an improved Canny edge detection algorithm is proposed by replacing the Gaussian filter with a bilateral filter. Also, a new approach for estimating Canny algorithm thresholds has been developed using the Flower Pollination algorithm. Subsequently, the improved Canny algorithm with a machine learning model was integrated to enhance edge detection accuracy. The performance of the improved algorithm was evaluated using 50 images from the Berkeley Computer Vision dataset. The experiment results show that the enhanced algorithm has an AUC of 0.81 for RF (Random Forest) and 0.75 for the LR (Logistic Regression) classifier, which can detect edges more accurately than the traditional Canny algorithm, which has an AUC of about 0.57. The proposed method sets a new standard for edge detection performance.